1978
DOI: 10.1159/000144903
|View full text |Cite
|
Sign up to set email alerts
|

Activity of phosphatases and succinic dehydrogenase in the trigeminal ganglion of the corticosteroid-treated mouse

Abstract: Immature mice were treated for 21 days with daily doses of triamcinolone diacetate. The trigeminal ganglion was studied enzymatically for the activity of alkaline phosphatase, acid phosphatase, ATPase and succinic dehydrogenase. It became apparent that the prolonged treatment with a potent corticosteroid hormone did not affect significantly the in vivo activity of the above enzymes. Some enzymes even appeared to have increased their intracellular activity. The heterogeneous effect of corticosteroid upon their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Dual embryonic origin (of epidermal placode and of neural crest origin) (Hamburger, 1961), as fixation artifacts (Cammermeyer, 1962), difference in central and peripheral projections (Preto Parvis, 1954), different sensory functions (Noden, 1980;Spassova, 1982), different histogenetic characteristics (Meyer et al, 1973), difference in distribution of cytoplasmic organelles and relative density of cytoplasm (Carmel and Stein, 1969;Matsuura et al, 1969), fluid shift between cells and the surrounding extracellular spaces (Moses, 1967), difference in functional activity have been offered as different hypotheses. Kalina and Wolman (1970), Peach (1972) and Silbermann and Finkelbrand (1978) found differences in chemical constituents in these two types of neurons in sensory ganglia of rodents. Similar observations have been reported in mammals (Cauna and Naik, 1963;Kalina and Bubis, 1969;Peach, 1972;Kishida et al, 1982).…”
Section: Introductionmentioning
confidence: 92%
“…Dual embryonic origin (of epidermal placode and of neural crest origin) (Hamburger, 1961), as fixation artifacts (Cammermeyer, 1962), difference in central and peripheral projections (Preto Parvis, 1954), different sensory functions (Noden, 1980;Spassova, 1982), different histogenetic characteristics (Meyer et al, 1973), difference in distribution of cytoplasmic organelles and relative density of cytoplasm (Carmel and Stein, 1969;Matsuura et al, 1969), fluid shift between cells and the surrounding extracellular spaces (Moses, 1967), difference in functional activity have been offered as different hypotheses. Kalina and Wolman (1970), Peach (1972) and Silbermann and Finkelbrand (1978) found differences in chemical constituents in these two types of neurons in sensory ganglia of rodents. Similar observations have been reported in mammals (Cauna and Naik, 1963;Kalina and Bubis, 1969;Peach, 1972;Kishida et al, 1982).…”
Section: Introductionmentioning
confidence: 92%
“…Studies in the chick and rat (Gaik and Farbman 1973;Peach, 1972) concluded that these two types are genuinely different from each other in terms of density and distribution of cytoplasmic organelles. Differences in chemical constituents in these two types of neurones in the trigeminal ganglion have been reported (Kalina and Bubis, 1969;Silbermann and Finkelbrand, 1978). The significance of these two populations of neurones has been the subject of considerable speculations.…”
Section: Introductionmentioning
confidence: 99%